K.H AHMAD DAHLAN TINJAUAN TERHADAP KONSEP PENDIDIKANNYA - SUGIATI SUGIATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Ahmad Dahlan is a figure in the religious reform movement in Indonesia, both in the socio-cultural, political, educational fields, as well as a national hero in the effort to pioneer the independence of the Republic of Indonesia. Efforts in reforming the field of education, he formulated an educational concept that integrates the education system of Islamic boarding schools with a modern education system that is in accordance with the demands of the times. KH. Ahmad Dahlan changed his education system, which originally consisted of dualism of education, into an education system that no longer differentiated between religious education and general education. KH. Ahmad Dahlan aspires to the formation of a generation of